Method for producing olefin polymers
Patent Information
- Application Number
- JP2022034776
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-31
- Filing Date
- 2022-03-07
- Publication Date
- 2026-09-08
- Estimated Expiration
- 2042-03-07
AI Technical Summary
【0029】 本発明では、ハフニウム錯体を用いてオレフィン重合体を製造するにあたり、ハフニウム錯体中に不純物として含まれるジルコニウム錯体を選択的に失活させ、得られる重合体中のジルコニウム錯体由来重合体量比を減らすことができる。
Smart Images

Figure 0007917301000022 
Figure 0007917301000023 
Figure 0007917301000001
Abstract
Description
[Technical Field]
[0001] The present invention relates to a method for producing olefin polymers, and more particularly to a method for producing olefin polymers using a transition metal catalyst. [Background technology]
[0002] In the production of olefin (co)polymers, catalysts consisting of transition metal complexes such as metallocenes and co-catalyst components such as organoaluminum oxy compounds (aluminoxanes) are widely used as catalysts for olefin polymerization. Various attempts have been made to adjust the physical properties of the resulting olefin polymers by carrying out olefin polymerization in the presence of various additives when using such catalysts.
[0003] For example, Patent Document 1 discloses that the melting point of the polymer obtained can be lowered by polymerizing ethylene using a metallocene-based supported catalyst in the presence of an ether or thioether. In the examples of Patent Document 1, it is specifically shown that ethylene / olefin copolymerization was obtained using a supported catalyst containing a zirconium compound or a titanium compound. However, Patent Document 1 does not specifically show polymerization using a supported catalyst containing two or more metallocene compounds, nor polymerization using a supported catalyst containing a hafnium compound.
[0004] In this regard, Patent Document 2 discloses that the melting point of the resulting polymer can be lowered by copolymerizing ethylene with other olefins using a Ziegler-Natta catalyst in the presence of an ether or thioether.
[0005] Furthermore, Patent Document 3 also discloses a method for producing olefin polymers, which involves polymerizing olefins in the presence of a metallocene-based supported catalyst and a specific thioether. Specifically, the examples in Patent Document 3 show the acquisition of ethylene / olefin copolymers using a supported catalyst containing a zirconium compound. The production method described in Patent Document 3 aims to produce highly active olefin polymers while ensuring stable polymerization by effectively preventing contamination of the polymerizer walls and internal components such as stirring blades. However, Patent Document 3 does not describe the use of a metallocene-based supported catalyst composed of multiple transition metal complexes, nor does it specifically describe polymerization using a supported catalyst containing a hafnium compound.
[0006] Furthermore, conventional methods have also employed the use of catalysts for olefin polymerization that combine two transition metal complexes with different properties. Attempts have also been made to carry out such olefin polymerization in the presence of various additives.
[0007] For example, Patent Document 4 discloses the polymerization of olefins using a catalyst that combines two transition metal complexes with different properties, carried out in the presence of compounds having active protons, such as polyalkylene oxide block polymers and higher aliphatic amides. However, Patent Document 4 does not describe the polymerization of olefins carried out in the presence of an ether in which two hydrocarbon groups are bonded to each other via one oxygen atom, or a thioether in which two hydrocarbon groups are bonded to each other via one sulfur atom. Furthermore, Patent Document 4 does not specifically describe polymerization using a supported catalyst containing a hafnium compound as a metallocene-based supported catalyst. [Prior art documents] [Patent Documents]
[0008] [Patent Document 1] Special Publication No. 2003-501527 [Patent Document 2] Special Publication No. 2003-501526 [Patent Document 3] Japanese Patent Publication No. 2020-164685 [Patent Document 4] Japanese Patent Publication No. 2014-019825 [Overview of the project] [Problems that the invention aims to solve]
[0009] Polymerization of olefins using catalysts for olefin polymerization that combine two types of transition metal complexes with different constituent metals is often actively performed to adjust the physical properties of the resulting olefin polymer. However, depending on the type of transition metal used, the second transition metal may be present as an impurity in the first transition metal constituting the transition metal complex. In this case as well, olefin polymerization is performed using catalysts for olefin polymerization that combine multiple types of transition metal complexes with different constituent metals. For example, when a hafnium complex is used as a catalyst for olefin polymerization, a zirconium complex may be present as an impurity in this catalyst. The present inventors have found that when olefin polymerization is performed using a catalyst for olefin polymerization that contains a corresponding zirconium complex in addition to a hafnium complex, (i) the zirconium complex tends to have higher activity as a polymerization catalyst than the hafnium complex, and (ii) the ratio of the amount of polymer produced from the zirconium complex to the amount of polymer produced from the hafnium complex tends to be greater than the ratio of the amount of zirconium complex to the amount of hafnium complex in the olefin polymerization catalyst.
[0010] When producing olefin polymers using hafnium complexes, polymers derived from zirconium complexes, which are impurities in the hafnium complexes, may be mixed in, potentially affecting the physical properties of the resulting polymers. Therefore, the present invention aims to provide a method for producing olefin polymers using an olefin polymerization catalyst containing hafnium complexes and zirconium complexes, which can reduce the amount of polymer derived from zirconium complexes produced. [Means for solving the problem]
[0011] The present inventors have discovered that when polymerizing olefins in a catalyst system containing a hafnium complex, adding a specific additive to the catalyst system can suppress the formation of polymers derived from zirconium complexes, which are impurities in the hafnium complex, while maintaining the activity of the hafnium complex to some extent, thus completing the present invention. In other words, the present invention relates to the following [1] to [9].
[0012] [1] A method for producing an olefin polymer, characterized by comprising the step of (co)polymerizing ethylene and one or more olefins selected from the group consisting of 3 to 20 carbon atoms in the presence of an olefin polymerization catalyst comprising the following components (A), (B), and (C), and the following component (D). Component (A): A hafnium compound represented by the following general formula (1);
[0013] [ka]
[0014] [In general formula (1), n is a number that satisfies the valence of Hf, R 1 ~R 8 Each of these independently consists of a hydrogen atom, a hydrocarbon group, a halogen-containing group, an oxygen-containing group, and a nitrogen atom. Contains groups, boron-containing groups, sulfur-containing groups, phosphorus-containing groups, silicon-containing groups, germanium-containing groups Selected from the group consisting of tin-containing groups, which may be the same or different from each other, R 1 ~R 8 of Two adjacent bases within this structure may be linked together to form a ring. Q 1 It is a divalent group, a hydrocarbon group with 1 to 20 carbon atoms, a halogen-containing group, or a silicon-containing group. a group containing a germanium group or a tin-containing group, wherein the hydrocarbon having 1 to 20 carbon atoms group may contain oxygen, each X is independently a hydrogen atom, a halogen atom, a hydrocarbon group, a halogen-containing hydrocarbon group, selected from the group consisting of a silicon-containing group, an oxygen-containing group, a sulfur-containing group, a nitrogen-containing group and a phosphorus-containing group is an atom or group obtained, and may be the same or different from each other.]] Component (B): a zirconium compound represented by the following general formula (2);
[0015]
Chemical Formula
[0016] [In general formula (2), n is a number satisfying the valence of Zr, R 9 to R 16 are each independently selected from the group consisting of a hydrogen atom, a hydrocarbon group, a halogen-containing group, an oxygen-containing group, a nitrogen-containing group, a boron-containing group, a sulfur-containing group, a phosphorus-containing group, a silicon-containing group, a germanium-containing group and a tin-containing group, and may be the same or different from each other, R 9 to R 16 two adjacent groups among them may be linked to form a ring, Q 2 is a divalent group, which is a hydrocarbon group having 1 to 20 carbon atoms, a halogen-containing group, a silicon-containing group, a germanium-containing group or a tin-containing group, and the hydrocarbon group having 1 to 20 carbon atoms may contain oxygen, each X is independently an atom or a group selected from the group consisting of a hydrogen atom, a halogen atom, a hydrocarbon group, a halogen-containing hydrocarbon group, a silicon-containing group, an oxygen-containing group, a sulfur-containing group, a nitrogen-containing group and a phosphorus-containing group, and may be the same or different from each other.]] Component (C): at least one compound selected from the group consisting of an organometallic compound (c-1) represented by the following general formulas (3) to (5), an organoaluminum oxy compound (c-2), and a compound (c-3) that reacts with component (A) and component (B) to form an ion pair; R a m Al(OR b ) n H p X q ···(3) [In general formula (3), R a and R b each independently represent a hydrocarbon group having 1 to 15 carbon atoms, X represents a halogen atom, m is a number satisfying 0<m≦3, n is a number satisfying 0≦n<3, p is a number satisfying 0≦p<3, q is a number satisfying 0≦q<3, and m+n+p+q=3.]] M a AlR a 4···(4) [In general formula (4), M a represents Li, Na or K, and R a represents a hydrocarbon group having 1 to 15 carbon atoms.]] R a r M b R b s X t ···(5) [In general formula (5), R a and R b each independently represent a hydrocarbon group having 1 to 15 carbon atoms, M b is selected from Mg, Zn and Cd, X represents a halogen atom, r is a number satisfying 0<r≦2, s is a number satisfying 0≦s≦1, t is a number satisfying 0≦t≦1, and r+s+t=2.]] Component (D): a compound represented by the following general formula (6); R 17 -E-R 18 ···(6) [In general formula (6), E represents a group 16 atom of the periodic table, R 17 and R 18 each independently represent a hydrocarbon group having 1 to 20 carbon atoms.]]
[0017] [2] The method for producing an olefin polymer according to claim 1, wherein in the general formula (6), E is an oxygen atom or a sulfur atom.
[0018] [3] In the above general formula (6), R 17 and R 18 A method for producing an olefin polymer according to [1] or [2], wherein each of the elements is an alkyl group having 1 to 20 carbon atoms.
[0019] [4] In the above general formula (6), R 17 and R 18 A method for producing an olefin polymer according to any one of [1] to [3], wherein each of is independently a linear alkyl group having 1 to 20 carbon atoms.
[0020] [5] In the above general formula (6), R 17 and R 18 A method for producing an olefin polymer according to any one of [1] to [4], wherein is a linear alkyl group having the same number of carbon atoms from 1 to 20.
[0021] [6] A method for producing an olefin polymer according to any one of [1] to [5], wherein the catalyst for olefin polymerization is in solid form.
[0022] [7] The method for producing an olefin polymer according to [6], wherein the catalyst for olefin polymerization further comprises a solid support (S).
[0023] [8] A method for producing an olefin polymer according to [7], wherein the component (C) is an organoaluminum oxy compound and the solid support (S) is a porous oxide.
[0024] [9] A method for producing an olefin polymer according to any one of [1] to [8], wherein component (A) is a hafnium compound represented by the following general formula (7), and component (B) is a zirconium compound represented by the following general formula (8).
[0025] [ka]
[0026] [In general formula (7), n is a number that satisfies the valence of Hf, R 19 ~R 30 Each of these is independently selected from the group consisting of hydrogen atoms, hydrocarbon groups, halogen-containing groups, oxygen-containing groups, nitrogen-containing groups, boron-containing groups, sulfur-containing groups, phosphorus-containing groups, silicon-containing groups, germanium-containing groups, and tin-containing groups, and they may be the same or different from each other, R 19 ~R 30 Two adjacent bases among them may be linked together to form a ring. Q 1 This is a divalent group, which is a hydrocarbon group having 1 to 20 carbon atoms, a halogen-containing group, a silicon-containing group, a germanium-containing group, or a tin-containing group, and the hydrocarbon group having 1 to 20 carbon atoms may contain oxygen. Each of X is an atom or group independently selected from the group consisting of hydrogen atoms, halogen atoms, hydrocarbon groups, halogen-containing hydrocarbon groups, silicon-containing groups, oxygen-containing groups, sulfur-containing groups, nitrogen-containing groups, and phosphorus-containing groups, and may be the same or different from one another.
[0027] [ka]
[0028] [In general formula (8), n is a number that satisfies the valence of Zr, R 31 ~R 42Each of these is independently selected from the group consisting of hydrogen atoms, hydrocarbon groups, halogen-containing groups, oxygen-containing groups, nitrogen-containing groups, boron-containing groups, sulfur-containing groups, phosphorus-containing groups, silicon-containing groups, germanium-containing groups, and tin-containing groups, and they may be the same or different from each other, R 31 ~R 42 Two adjacent bases among them may be linked together to form a ring. Q 2 This is a divalent group, which is a hydrocarbon group having 1 to 20 carbon atoms, a halogen-containing group, a silicon-containing group, a germanium-containing group, or a tin-containing group, and the hydrocarbon group having 1 to 20 carbon atoms may contain oxygen. Each of X is an atom or group independently selected from the group consisting of hydrogen atoms, halogen atoms, hydrocarbon groups, halogen-containing hydrocarbon groups, silicon-containing groups, oxygen-containing groups, sulfur-containing groups, nitrogen-containing groups, and phosphorus-containing groups, and may be the same or different from one another. [Effects of the Invention]
[0029] In this invention, when producing an olefin polymer using a hafnium complex, the zirconium complex contained as an impurity in the hafnium complex can be selectively deactivated, thereby reducing the proportion of polymer derived from the zirconium complex in the resulting polymer. [Brief explanation of the drawing]
[0030] [Figure 1] This figure shows the relationship between the proportion of polymers derived from component (A) and component (B) obtained by copolymerization and the amount of component (D) added in Examples 1 and 2, and Production Example 3. [Figure 2] This figure shows the relationship between the proportion of polymers derived from component (A) and component (B) obtained by copolymerization and the amount of component (D) added in Example 3 and Production Example 6. [Modes for carrying out the invention]
[0031] The following describes specific embodiments of the present invention in detail, but the present invention is not limited in any way to the following embodiments and can be implemented with appropriate modifications within the scope of the object of the present invention.
[0032] In this specification, unless otherwise specified, the terms "polymerization" and "(co)polymerization" are used to encompass both homopolymerization and copolymerization. Furthermore, in this specification, a numerical range represented by "~" means a range that includes the numbers written before and after "~" as the lower and upper limits, respectively.
[0033] [Method for producing olefin polymers] The method for producing an olefin polymer according to the present invention includes a step of (co)polymerizing ethylene and one or more olefins selected from the group consisting of α-olefins having 3 to 20 carbon atoms in the presence of an olefin polymerization catalyst described later and component (D) described later. This (co)polymerization is usually carried out in a polymerization reactor. The manufacturing method according to the present invention will be described in detail below.
[0034] <Catalyst for olefin polymerization> In the manufacturing method of the present invention, an olefin polymerization catalyst comprising the following components (A), (B), and (C) is used. This olefin polymerization catalyst is preferably in solid form. In addition to components (A), (B), and (C), this olefin polymerization catalyst may also contain a solid support (S), and may further contain component (G). The components used in the above-mentioned olefin polymerization catalyst will be explained below.
[0035] Ingredient (A) In this invention, a hafnium complex is used as component (A) of the catalyst for olefin polymerization. Specifically, component (A) used in this invention is a hafnium compound represented by the following general formula (1):
[0036] [ka]
[0037] In the general formula (1) above, n is a number that satisfies the valence of Hf, and specifically an integer from 1 to 4, preferably 2. R 1 ~R 8 Each of these groups is independently selected from the group consisting of hydrogen atoms, hydrocarbon groups, halogen-containing groups, oxygen-containing groups, nitrogen-containing groups, boron-containing groups, sulfur-containing groups, phosphorus-containing groups, silicon-containing groups, germanium-containing groups, and tin-containing groups, and they may be the same or different from each other.
[0038] Examples of hydrocarbon groups include alkyl groups, cycloalkyl groups, alkenyl groups, aryl groups, and arylalkyl groups. Examples of alkyl groups include methyl groups, ethyl groups, n-propyl groups, isopropyl groups, n-butyl groups, isobutyl groups, s-butyl groups, t-butyl groups, n-pentyl groups, neopentyl groups, n-hexyl groups, n-octyl groups, nonyl groups, dodecyl groups, and eicosyl groups. Examples of cycloalkyl groups include cyclopropyl groups, cyclobutyl groups, cyclopentyl groups, cyclohexyl groups, norbornyl groups, and adamantyl groups. Examples of alkenyl groups include vinyl groups, propenyl groups, and cyclohexenyl groups. Examples of aryl groups include phenyl, tolyl, dimethylphenyl, trimethylphenyl, ethylphenyl, propylphenyl, α- or β-naphthyl, methylnaphthyl, anthracenyl, phenanthryl, benzylphenyl, pyrenyl, acenaphthyl, phenalenyl, aceantrilenyl, tetrahydronaphthyl, indanyl, and biphenylyl groups. Examples of arylalkyl groups include benzyl, phenylethyl, and phenylpropyl groups.
[0039] Examples of the silicon-containing groups include alkylsilyl groups such as methylsilyl group, dimethylsilyl group, trimethylsilyl group, ethylsilyl group, diethylsilyl group, triethylsilyl group, and dimethyl-tert-butylsilyl group; and arylsilyl groups such as dimethylphenylsilyl group, diphenylmethylsilyl group, and triphenylsilyl group.
[0040] The aforementioned R 1 ~R 8 Two adjacent groups among them may be linked to form a ring. Here, in one preferred embodiment of the present invention, R 5 and R 6 , and, R 7 and R 8 They are all connected to each other, forming a ring.
[0041] Q 1 The group is a divalent group, which is a hydrocarbon group having 1 to 20 carbon atoms, a halogen-containing group, a silicon-containing group, a germanium-containing group, or a tin-containing group, and the hydrocarbon group having 1 to 20 carbon atoms may contain oxygen.
[0042] Q 1 Examples of hydrocarbon groups with 1 to 20 carbon atoms that may contain oxygen include alkylidene groups with 1 to 20 carbon atoms such as methylene group, 1,2-ethylidene group, 1,2-ethylidene group, and isopropylidene group; methylene groups with 13 to 20 carbon atoms having two or more aryl groups such as diphenylmethylene group and di(p-tolyl)methylene group; and di(alkoxyphenyl)methylene groups with 15 to 20 carbon atoms such as di(p-methoxyphenyl)methylene group.
[0043] Q 1Examples of silicon-containing groups that can become these include silylene, methylsilylene, dimethylsilylene, diisopropylsilylene, dibutylsilylene, methylbutylsilylene, methyl-t-butylsilylene, dicyclohexylsilylene, methylcyclohexylsilylene, methylphenylsilylene, diphenylsilylene, ditylsilylene, methylnaphthylsilylene, dinaphthylsilylene, cyclodimethylenesilylene, cyclotrimethylenesilylene, cyclotetramethylenesilylene, cyclopentamethylenesilylene, cyclohexamethylenesilylene, and cycloheptamethylenesilylene. Particularly preferred are dialkylsilylene groups such as dimethylsilylene and dibutylsilylene.
[0044] In one particularly preferred embodiment of the present invention, Q 1 Q is a di(p-methoxyphenyl)methylene group. In another particularly preferred embodiment of the present invention, Q 1 This is a di(p-tolyl)methylene group. Each X is an atom or group independently selected from the group consisting of hydrogen atoms, halogen atoms, hydrocarbon groups, halogen-containing hydrocarbon groups, silicon-containing groups, oxygen-containing groups, sulfur-containing groups, nitrogen-containing groups, and phosphorus-containing groups, preferably halogen atoms or hydrocarbon groups. Examples of halogen atoms include fluorine, chlorine, bromine, and iodine, with chlorine being particularly preferred. Furthermore, if n is 2 or more, the multiple groups represented by X may be the same or different from each other. Also, if there are multiple groups represented by X, these multiple Xs may bond to each other to form a ring.
[0045] In a preferred and exemplary embodiment of the present invention, component (A) used in the present invention is a hafnium compound represented by the following general formula (7).
[0046] [ka]
[0047] In the above general formula (7), n is the same as n in the above general formula (1). R 19 ~R 30 Each of these is independently selected from the group consisting of a hydrogen atom, a hydrocarbon group, a halogen-containing group, an oxygen-containing group, a nitrogen-containing group, a boron-containing group, a sulfur-containing group, a phosphorus-containing group, a silicon-containing group, a germanium-containing group, and a tin-containing group, and may be the same or different from each other. Here, R 19 ~R 30 Examples of hydrocarbon groups and silicon-containing groups that can become R in the general formula (1) are 1 ~R 8 These are similar to the hydrocarbon groups and silicon-containing groups that can become such groups, respectively.
[0048] The aforementioned R 19 ~R 30 Two adjacent groups among them may be linked to form a ring. Here, in one preferred embodiment of the present invention, R 24 and R 25 , and, R 28 and R 29 They are all connected to each other, forming a ring.
[0049] Q 1 And X are, respectively, Q in the general formula (1) above. 1 And it is the same as X. In one particularly preferred embodiment of the present invention, component (A) used in the present invention is a hafnium compound represented by the following general formula (9).
[0050] [ka]
[0051] In the above general formula (9), n, Q 1 And X are n and Q in the general formula (1) above, respectively. 1 And it is the same as X. Furthermore, in another particularly preferred embodiment of the present invention, component (A) used in the present invention is a hafnium compound represented by the following general formula (11). [ka]
[0052] In the above general formula (11), n and Q 1 and X are the same as n, Q 1 and X in the above general formula (1), respectively.
[0053] Ingredient (B) In the present invention, component (B) that constitutes the olefin polymerization catalyst is a zirconium complex. Specifically, component (B) used in the present invention is a zirconium compound represented by the following general formula (2):
[0054]
Chemical Formula
[0055] In the above general formula (2), n is a number satisfying the valence of Zr, and specifically is an integer of 1 to 4, preferably 2. R 9 to R 16 are each independently selected from the group consisting of a hydrogen atom, a hydrocarbon group, a halogen-containing group, an oxygen-containing group, a nitrogen-containing group, a boron-containing group, a sulfur-containing group, a phosphorus-containing group, a silicon-containing group, a germanium-containing group and a tin-containing group, and may be the same or different from each other. Here, examples of the hydrocarbon group and silicon-containing group that can be R 9 to R 16 are respectively the same as the examples of the hydrocarbon group and silicon-containing group that can be R 1 to R 8 in the above general formula (1).
[0056] Of R 9 to R 16 , two adjacent groups may be linked to each other to form a ring. Here, in one preferred embodiment of the present invention, R 13 and R 14 , and R 15 and R 16 are each linked to each other to form a ring.
[0057] Q 2is a divalent group, and is a hydrocarbon group having 1 to 20 carbon atoms, a halogen-containing group, a silicon-containing group, a germanium-containing group or a tin-containing group, and the hydrocarbon group having 1 to 20 carbon atoms may contain oxygen. Here, Q 2 Examples of the hydrocarbon group having 1 to 20 carbon atoms and the silicon-containing group which can be Q are the same as examples of the hydrocarbon group and the silicon-containing group which can be Q 1 in the general formula (1), respectively.
[0058] Each X is independently an atom or a group selected from the group consisting of a hydrogen atom, a halogen atom, a hydrocarbon group, a halogen-containing hydrocarbon group, a silicon-containing group, an oxygen-containing group, a sulfur-containing group, a nitrogen-containing group and a phosphorus-containing group, preferably a halogen atom or a hydrocarbon group. Examples of the halogen atom include fluorine, chlorine, bromine and iodine, with chlorine being particularly preferred. When n is 2 or more, a plurality of groups represented by X may be the same or different from each other. When a plurality of groups represented by X are present, the plurality of X groups may be bonded to each other to form a ring.
[0059] In a preferred exemplary embodiment of the present invention, component (B) used in the present invention is a zirconium compound represented by the following general formula (8).
[0060]
Chemical Formula
[0061] In the general formula (8), n is the same as n in the general formula (2). R 31 to R 42 are each independently selected from the group consisting of a hydrogen atom, a hydrocarbon group, a halogen-containing group, an oxygen-containing group, a nitrogen-containing group, a boron-containing group, a sulfur-containing group, a phosphorus-containing group, a silicon-containing group, a germanium-containing group and a tin-containing group, and may be the same or different from each other. Here, R 31 to R 42 Examples of the hydrocarbon group and the silicon-containing group which can be R1 to R6 are the same as examples of the hydrocarbon group and the silicon-containing group which can be R 9 to R 16These are similar to the hydrocarbon groups and silicon-containing groups that can become such groups, respectively.
[0062] The aforementioned R 31 ~R 42 Two adjacent groups among them may be linked to form a ring. Here, in one preferred embodiment of the present invention, R 36 and R 37 , and, R 40 and R 41 They are all connected to each other, forming a ring.
[0063] Q 2 And X are, respectively, Q in the general formula (2) above. 2 And it is the same as X. In one particularly preferred embodiment of the present invention, component (B) used in the present invention is a zirconium compound represented by the following general formula (10).
[0064] [ka]
[0065] In the above general formula (10), n, Q 2 And X are n and Q in the general formula (2) above, respectively. 2 And it is the same as X. Furthermore, in another particularly preferred embodiment of the present invention, component (B) used in the present invention is a zirconium compound represented by the following general formula (12). [ka]
[0066] In the above general formula (12), n, Q 2 And X are n and Q in the general formula (2) above, respectively. 2 And it is the same as X. In one typical embodiment of the present invention, the manufacturing method of the present invention is performed when producing an olefin polymer using a hafnium catalyst containing component (B) as an impurity in addition to component (A). In this embodiment, the ligand constituting component (B) is often the same as the ligand constituting component (A). Therefore, in one exemplary embodiment of the present invention, R in the general formula (2) 9 ~R 16 , n, Q 2 and X are, respectively, R in the general formula (1) above. 1 ~R 8 , n, Q 1 And it is the same as X. However, R in the general formula (2) above 9 ~R 16 , n, Q 2 And all of X are not necessarily R in the general formula (1) above. 1 ~R 8 , n, Q 1 And it does not have to be the same as X; for example, R in the general formula (2) above 9 ~R 16 , n, Q 2 And one or more of X are R in the general formula (1) above. 1 ~R 8 , n, Q 1 And may be different from X. The same applies to R in general formula (8). 31 ~R 42 , n, Q 2 and X and R in the above general formula (7) 19 ~R 30 , n, Q 1 and its relationship with X, n and Q in the general formula (10) above. 2 and X and n, Q in the general formula (9) above. 1 The relationship between and X, and n and Q in the above general formula (12). 2 and X and n and Q in the general formula (11) above. 1 This also applies to the relationship with X.
[0067] Ingredients (C) In the olefin polymerization catalyst used in the present invention, a specific organoaluminum compound is used as component (C) in addition to the aforementioned component (A) and the aforementioned component (B). This component (C) functions as a co-catalyst, and is specifically at least one compound selected from the group consisting of an organometallic compound represented by the following general formulas (3) to (5) (c-1), an organoaluminum oxy compound (c-2), and a compound (c-3) that reacts with component (A) and component (B) to form an ion pair; R a m Al(OR b ) n H p X q ···(3) [In general formula (3), R a and R b each independently represent a hydrocarbon group having 1 to 15 carbon atoms, X represents a halogen atom, m is a number satisfying 0 < m ≦ 3, n is a number satisfying 0 ≦ n < 3, p is a number satisfying 0 ≦ p < 3, q is a number satisfying 0 ≦ q < 3, and m + n + p + q = 3.]] M a AlR a 4···(4) [In general formula (4), M a represents Li, Na or K, and R a represents a hydrocarbon group having 1 to 15 carbon atoms.]] R a r M b R b s X t ···(5) [In general formula (5), R a and R b each independently represent a hydrocarbon group having 1 to 15 carbon atoms, M b is selected from Mg, Zn and Cd, X represents a halogen atom, r is a number satisfying 0 < r ≦ 2, s is a number satisfying 0 ≦ s ≦ 1, t is a number satisfying 0 ≦ t ≦ 1, and r + s + t = 2.]] Among the organometallic compounds (c-1) represented by general formulas (3), (4), or (5), those represented by general formula (3) are preferred, specifically trialkylaluminum compounds such as trimethylaluminum, triethylaluminum, triisopropylaluminum, triisobutylaluminum, trihexylaluminum, and trioctylaluminum; as well as alkylaluminum hydrides such as dimethylaluminum hydride, diethylaluminum hydride, diisopropylaluminum hydride, di-n-butylaluminum hydride, diisobutylaluminum hydride, and diisohexylaluminum hydride. These can be used individually or in combination of two or more.
[0068] As the organoaluminum oxy compound (c-2), organoaluminum oxy compounds prepared from trialkylaluminum or tricycloalkylaluminum are preferred, and aluminoxanes prepared from trimethylaluminum or triisobutylaluminum are particularly preferred. Such organoaluminum oxy compounds can be used individually or in combination of two or more.
[0069] As the compound (c-3) that reacts with component (A) and component (B) to form an ion pair, Lewis acids, ionic compounds, borane compounds, and carborane compounds described in Japanese Patent Publication No. 1-501950, Japanese Patent Publication No. 1-502036, Japanese Patent Application Publication No. 3-179005, Japanese Patent Application Publication No. 3-179006, Japanese Patent Application Publication No. 3-207703, Japanese Patent Application Publication No. 3-207704, and US5321106, etc., heteropoly compounds and isopoly compounds can be used without limitation. In the present invention, component (C) is preferably the organoaluminum oxy compound (c-2).
[0070] Solid carrier (S) The olefin polymerization catalyst used in the present invention may further contain a solid support (S) in addition to the components (A), (B), and (C) mentioned above. In a preferred embodiment of the present invention, the olefin polymerization catalyst further contains a solid support (S). The solid support (S) that can be used in the present invention is an inorganic or organic compound, and is in the form of a granular or particulate solid.
[0071] Examples of inorganic compounds include porous oxides, inorganic chlorides, clays, clay minerals, or ion-exchangeable layered compounds, with porous oxides being preferred. Porous oxides include SiO2, Al2O3, MgO, ZrO, TiO2, B2O3, CaO, ZnO, BaO, and ThO2, or composites or mixtures containing these, specifically natural or synthetic zeolites, SiO2-MgO, SiO2-Al2O3, SiO2-TiO2, SiO2-V2O5, SiO2-Cr2O3, and SiO2-TiO2-MgO. Of these, those with SiO2 as the main component are preferred.
[0072] Such porous oxides have different properties depending on the type and manufacturing method, but the solid carrier used in the present invention has a particle size of typically 0.2 to 300 μm, preferably 1 to 200 μm, and a specific surface area of typically 50 to 1200 m². 2 / g, preferably 100-1000m 2 It is in the range of / g, and the pore volume is typically 0.3-30 cm³. 3 A range of / g is preferred. Such a carrier may be used after being calcined, if necessary, for example, at 100 to 1000°C, preferably 150 to 700°C. In the present invention, the solid carrier (S) is preferably the porous oxide.
[0073] Ingredients (G) The olefin polymerization catalyst used in the present invention may further contain, in addition to the components (A), (B), and (C) and an optional solid support (S), a polyalkylene oxide alkyl ether as component (G).
[0074] In the present invention, such component (G) can be coexisted in the catalyst for olefin polymerization for the purpose of suppressing fouling in the reactor or improving the particulate properties of the resulting polymer. An example of the polyalkylene oxide alkyl ether is polyoxyethylene lauryl ether.
[0075] Method for producing catalysts for olefin polymerization This paper describes a method for preparing the catalyst for olefin polymerization used in the present invention. The olefin polymerization catalyst used in the present invention can be prepared by adding component (A), component (B), and component (C) to an inert hydrocarbon or to a polymerization system using an inert hydrocarbon.
[0076] The order in which each component is added is arbitrary, but a preferred order is, for example, i) A method in which component (A) and component (B) are mixed and brought into contact, and then component (C) is brought into contact and added to the polymerization system. ii) A method of adding a contact product obtained by mixing and contacting component (A) and component (C), and a contact product obtained by mixing and contacting component (B) and component (C) into a polymerization system. iii) A method in which components (A), (B), and (C) are sequentially added to the polymerization system, etc.
[0077] Furthermore, if the olefin polymerization catalyst includes a solid support (S), a solid catalyst component (X) can be prepared by contacting at least one of components (A), (B), and (C) with the solid support (S) in an inert hydrocarbon. The order in which the components are contacted is arbitrary, but a preferred order is, for example, iv) A method for preparing a solid catalyst component (X) by contacting component (C) with a solid support (S), and then contacting components (A) and (B). v) A method of preparation by mixing and contacting components (A), (B), and (C), and then contacting them with a solid carrier (S). vi) A method using a solid catalyst component (X1) prepared by contacting component (C) with a solid support (S) and then with component (A), and a solid catalyst component (X2) prepared by contacting component (C) with a solid support (S) and then with component (B), is one example, and the more preferred method is iv).
[0078] Here, if the olefin polymerization catalyst also contains component (G), component (G) may be present in any step of the preparation of the olefin polymerization catalyst, and the order of contact is arbitrary. For example, if the contact order of each component is as described in iv) above, component (G) can be added after the contact of components (A) and (B).
[0079] Examples of inert hydrocarbons include, specifically, aliphatic hydrocarbons such as propane, butane, pentane, hexane, heptane, octane, decane, dodecane, and kerosene; alicyclic hydrocarbons such as cyclopentane, cyclohexane, and methylcyclopentane; aromatic hydrocarbons such as benzene, toluene, and xylene; and halogenated hydrocarbons such as ethylene chloride, chlorobenzene, and dichloromethane, or mixtures thereof.
[0080] The contact time between component (C) and the solid carrier (S) is typically 0 to 20 hours, preferably 0 to 10 hours, and the contact temperature is typically -50 to 200°C, preferably -20 to 120°C. The molar ratio of the contact between component (C) and the solid carrier (S) (component (C) / solid carrier (S)) is typically 0.2 to 2.0, particularly preferably 0.4 to 2.0.
[0081] The contact time between the contact material of component (C) and the solid carrier (S) and component (A) and component (B) is usually 0 to 5 hours, preferably 0 to 2 hours, and the contact temperature is usually -50 to 200°C, preferably -50 to 100°C. The amount of contact between component (A) and component (B) largely depends on the type and amount of component (C). When component (c-1) is used, the amount used is such that the molar ratio [(c-1) / M] of all transition metal atoms (M) in components (A) and (B) to component (c-1) is usually 0.01 to 100,000, preferably 0.05 to 50,000. When component (c-2) is used, the amount used is such that the molar ratio [(c-2) / M] of aluminum atoms in component (c-2) to all transition metal atoms (M) in components (A) and (B) is usually 10 to 500,000, preferably 20 to 100,000. When component (c-3) is used, the amount used is such that the molar ratio [(c-3) / M] of component (c-3) to all transition metal atoms (M) in components (A) and (B) is usually 1 to 10, preferably 1 to 5. The ratio of component (C) to the total number of transition metal atoms (M) in components (A) and (B) is determined by inductively coupled plasma (ICP) emission spectroscopy.
[0082] The ratio of component (A) to component (B) used can be arbitrarily determined from the molecular weight and molecular weight distribution of the olefin polymer, but the molar ratio of component (A) to the total of component (B) is usually 40 to 99.9%. Here, in one typical embodiment of the present invention, the manufacturing method of the present invention is carried out in a situation where the amount of component (A) is sufficiently greater than the amount of component (B). In such an embodiment, the molar ratio is preferably 80 to 99.9%, more preferably 90 to 99.9%. However, depending on the circumstances under which the manufacturing method of the present invention is carried out, this does not prevent the manufacturing method of the present invention from being carried out in a manner in which the amounts of component (A) and component (B) are equal or close to equal, for example, the molar ratio may be 40 to 60%.
[0083] The olefin polymerization catalyst described above may also be a prepolymerization catalyst component obtained by prepolymerizing an olefin. The prepolymerization catalyst component is formed from an olefin polymerization catalyst and an olefin polymer produced by prepolymerization as needed. The prepolymerization catalyst includes components (A), (B), and (C), an optional solid support (S), and an optional component (G), and an olefin polymer produced by prepolymerization as needed. A method for preparing the prepolymerization catalyst is, for example, to prepolymerize a small amount of olefin into a solid catalyst component obtained by contact as described in any of i) to vi) above. Specific examples of inert hydrocarbon solvents used in the preparation of the prepolymerization catalyst include those similar to the inert hydrocarbons described above.
[0084] The olefin used during prepolymerization preferably contains 100 to 0 mol% ethylene, 0 to 49 mol% propylene, and 0 to 100 mol% of an olefin with 4 or more carbon atoms; more preferably 100 to 0 mol% ethylene, 0 to 20 mol% propylene, and 0 to 100 mol% of an olefin with 4 or more carbon atoms; more preferably 100 to 20 mol% ethylene, 0 to 20 mol% propylene, and 0 to 80 mol% of an olefin with 4 or more carbon atoms; and most preferably 100 to 20 mol% ethylene and 0 to 80 mol% of an olefin with 4 or more carbon atoms.
[0085] Examples of olefins with four or more carbon atoms include α-olefins with 4 to 20 carbon atoms, such as 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene. Furthermore, cyclopentene, cycloheptene, norbornene, 5-methyl-2-norbornene, tetracyclododecene, 2-methyl-1,4,5,8-dimethano-1,2,3,4,4a,5,8,8a-octahydronaphthalene, styrene, vinylcyclohexane, and dienes can also be used.
[0086] When preparing the prepolymerization catalyst, components (A) and (B) are typically used in amounts of 0.001 to 1.0 mmol, preferably 0.005 to 0.5 mmol, per gram of solid support (S). Component (C) is typically used in amounts of 0.1 to 100 mmol, preferably 0.5 to 20 mmol, based on the amount of metal atoms contained in component (C).
[0087] In the prepolymerization catalyst obtained as described above, it is desirable that components (A) and (B) are supported on 1 g of solid support (S) in amounts of 0.005 to 1.0 mmol, preferably 0.01 to 0.3 mmol, component (C) is supported in amounts of approximately 1.0 to 100 mmol, preferably 2.0 to 50 mmol, in terms of the metal atoms contained in component (C), and that the olefin polymer produced by prepolymerization is supported in amounts of approximately 0.1 to 500 g, preferably 0.3 to 300 g, and particularly preferably 1 to 100 g.
[0088] <Ingredient (D)> When (co)polymerizing ethylene and one or more olefins selected from the group consisting of 3 to 20 carbon atoms using the olefin polymerization catalyst containing component (A) and component (B), the resulting polymer includes a polymer produced by the catalytic reaction of component (A) (hereinafter referred to as "component (A)-derived polymer") and a polymer produced by the catalytic reaction of component (B) (hereinafter referred to as "component (B)-derived polymer"). In such (co)polymerization, component (B) tends to have higher activity as a polymerization catalyst than component (A), and the ratio of the amount of component (A)-derived polymer produced to the amount of component (B)-derived polymer produced tends to be greater than the ratio of the amount of component (B) to the amount of component (A) in the olefin polymerization catalyst. In the production method of the present invention, by carrying out this (co)polymerization in the presence of a specific additive, it is possible to suppress the production of component (B)-derived polymer while maintaining the amount of component (A)-derived polymer produced to some extent. The ratio of polymer derived from component (A) to polymer derived from component (B) in the resulting polymer can be determined by the method described in "Method for measuring the ratio of polymer derived from component (A) to polymer derived from component (B)" in the following examples.
[0089] In this invention, such an additive is used as component (D). Specifically, component (D) is a compound represented by the following general formula (6): R 17 -ER 18 ...(6) [In general formula (6), E represents a group 16 atom of the periodic table, and R 17 and R 18 Each of these independently represents a hydrocarbon group with 1 to 20 carbon atoms. The inventors hypothesize that the effect of suppressing the generation of polymers derived from component (B) while maintaining the amount of polymers derived from component (A) to some extent is brought about by component (D) selectively reducing the catalytic activity of component (B) while maintaining the catalytic activity of component (A).
[0090] Here, in formula (6), E is preferably an oxygen atom or a sulfur atom. The aforementioned R 17 and R 18 The hydrocarbon groups constituting R may be saturated or unsaturated, aliphatic or aromatic, and linear, branched or cyclic. For example, any aliphatic hydrocarbon group such as alkyl or alkenyl groups, or any aromatic hydrocarbon group can be used. 17 and R 18 Each of these is independently preferably an alkyl group having 1 to 20 carbon atoms, and more preferably a linear alkyl group having 1 to 20 carbon atoms.
[0091] Here, the R 17 and R 18 They may be the same, or they may be different from each other. However, in the present invention, the R 17 and R 18 It is preferable that they are the same, and more preferably they are the same linear alkyl group having 1 to 20 carbon atoms.
[0092] Preferred specific examples of the compound represented by the general formula (6) include dibutyl ether, dioctyl ether, dicetyl ether, dibutyl sulfide, dicetyl sulfide, and the like, with dibutyl ether being particularly preferred.
[0093] The amount of component (D) used is preferably 1 to 500 ppm, more preferably 1 to 300 ppm, and particularly preferably 3 to 100 ppm, based on the amount of olefin polymer obtained.
[0094] <Method for producing olefin polymers> The method for producing an olefin polymer according to the present invention includes the step of (co)polymerizing ethylene and one or more olefins selected from the group consisting of 3 to 20 carbon atoms in the presence of the olefin polymerization catalyst and component (D).
[0095] Polymerization can be carried out in a suspension, solution, or gas phase, and is particularly preferred in a suspension or gas phase by slurry polymerization or gas phase polymerization. Specific examples of inert hydrocarbon media used in slurry polymerization include aliphatic hydrocarbons such as propane, butane, pentane, hexane, heptane, octane, decane, dodecane, and kerosene; alicyclic hydrocarbons such as cyclopentane, cyclohexane, and methylcyclopentane; aromatic hydrocarbons such as benzene, toluene, and xylene; halogenated hydrocarbons such as ethylene chloride, chlorobenzene, and dichloromethane, or mixtures thereof. Among these, aliphatic hydrocarbons and alicyclic hydrocarbons are preferred. The olefin itself can also be used as a solvent.
[0096] The polymerization temperature is typically -50 to 150°C, preferably 0 to 100°C, for slurry polymerization, and typically 0 to 120°C, preferably 20 to 100°C, for gas-phase polymerization. The polymerization pressure is typically atmospheric pressure to 10 MPa gauge pressure, preferably atmospheric pressure to 5 MPa gauge pressure. The polymerization reaction can be carried out by batch, semi-continuous, or continuous methods.
[0097] Polymerization can also be carried out in two or more stages with different reaction conditions. The molecular weight of the resulting olefin polymer can also be adjusted by introducing hydrogen into the polymerization system or by changing the polymerization temperature.
[0098] Specific examples of ethylene and α-olefins having 3 to 20 carbon atoms include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene. These can be used individually or in combination of two or more. In addition to ethylene and α-olefins having 3 to 20 carbon atoms, other copolymerization monomers may also be used in combination. Examples of copolymerization monomers include cyclopentene, cycloheptene, norbornene, 5-methyl-2-norbornene, tetracyclododecene, and 2-methyl-1,4,5,8-dimethano-1,2,3,4,4a,5,8,8a-octahydronaphthalene. Styrene, vinylcyclohexane, and dienes can also be used.
[0099] As the olefin, it is preferable to use ethylene alone or ethylene and an α-olefin having 3 to 20 carbon atoms. In particular, it is preferable to use ethylene in a range of 100 to 0 mol%, propylene in a range of 0 to 49 mol%, and an olefin having 4 or more carbon atoms in a range of 0 to 100 mol%, more preferably in a range of 100 to 0 mol%, propylene in a range of 0 to 20 mol%, and an α-olefin having 4 or more carbon atoms in a range of 0 to 100 mol%, particularly preferably in a range of 100 to 20 mol%, propylene in a range of 0 to 20 mol%, and an α-olefin having 4 or more carbon atoms in a range of 0 to 80 mol%, and most preferably in a range of 100 to 20 mol% and an α-olefin having 4 or more carbon atoms in a range of 0 to 80 mol%. Furthermore, in the present invention, it is preferable to produce an ethylene-based polymer with ethylene as the main monomer, and as the ethylene-based polymer, a (co)polymer containing 50 mol% or more of the ethylene component and optionally containing an α-olefin component having 4 to 10 carbon atoms is preferred.
[0100] During polymerization, the components (A) and (B) constituting the olefin polymerization catalyst are typically expressed in quantities of 10 per liter of polymerization volume, calculated based on the total number of transition metal atoms in components (A) and (B). -8 ~10 -3 moles, preferably 10 -7 ~10 -4 It is preferable to use it in molar quantities. The amount of component (C) is preferably 10 to 500 moles, more preferably 20 to 200 moles, per mole of transition metal atoms in component (A) and component (B), based on the amount of metal atoms contained in component (C).
[0101] Since component (D) tends to sufficiently adjust the MFR of the resulting olefin polymer, it is desirable to use it in an amount of 1 ppm by mass or more relative to the yield of the olefin polymer. On the other hand, since it tends to suppress increased load on the recovery and purification processes of the polymerization solvent and gas, and a decrease in catalyst performance, it is desirable to use it in an amount of 500 ppm by mass or less. The amount of component (D) used is more preferably 1 ppm by mass or more and 300 ppm by mass or less, and particularly preferably 3 ppm by mass or more and 100 ppm by mass or less. [Examples]
[0102] The present invention will be described in more detail below based on examples, but the present invention is not limited in any way to these examples.
[0103] [Synthesis of components (A) and (B)] <Synthesis Example 1> [Bis(4-methoxyphenyl)methylene(η) shown in the following formula (A-1) 5 -cyclopentadienyl)(η 5 -Tetramethyloctahydrodibenzofluorenyl)hafnium dichloride (hereinafter also referred to as "component (A-1)") was synthesized according to the method described in WO2015 / 122414.
[0104] [ka]
[0105] <Synthesis Example 2> The [bis(4-methoxyphenyl)methylene(η5-cyclopentadienyl)(η5-tetramethyloctahydrodibenzofluorenyl)] zirconium dichloride (hereinafter also referred to as "component (B-1)") represented by the following formula (B-1) was synthesized in the same manner as in Synthesis Example 1 above, except that hafnium tetrachloride was replaced with zirconium tetrachloride.
[0106] [ka]
[0107] <Synthesis Example 3> [Di(p-tril)methylene(η) shown in the following formula (A-2) 5 -cyclopentadienyl)(η 5 -Octamethyloctahydrodibenzofluorenyl)hafnium dichloride (hereinafter also referred to as "component (A-2)") is described in Japanese Patent Application Publication No. 2008-231266 as [di(p-tolyl)methylene(η 5 -cyclopentadienyl)(η 5 In the method for synthesizing [-octamethyloctahydrodibenzofluorenyl] zirconium dichloride, the method is the same as described in Japanese Patent Application Publication No. 2008-231266, except that zirconium tetrachloride is replaced with hafnium tetrachloride. 5 -cyclopentadienyl)(η 5 [Octamethyloctahydrodibenzofluorenyl] was synthesized using the same method as for the synthesis of zirconium dichloride. [ka]
[0108] <Synthesis Example 4> [Di(p-tril)methylene(η) shown in the following formula (B-2) 5 -cyclopentadienyl)(η 5-Octamethyloctahydrodibenzofluorenyl)zirconium dichloride (hereinafter also referred to as "component (B-2)") was synthesized based on the method described in Japanese Patent Application Publication No. 2008-231266. [ka]
[0109] [Synthesis of solid catalyst component (X)] <Synthesis Example 5> In a reactor with a stirrer and an internal volume of 270 L, under a nitrogen atmosphere, silica (average particle size 70 μm, specific surface area 340 m²) manufactured by Fuji Silicia Co., Ltd. was used as the solid support (S). 2 / g, pore volume 1.3cm 3 10 kg of (calcined at 250°C) was suspended in 77 L of toluene and then cooled to 0-5°C. 20.4 L of a toluene solution of methylaluminoxane (3.5 mol / L in terms of Al atoms) was added dropwise to this suspension as component (C) over 30 minutes. During this time, the temperature in the system was maintained at 0-5°C. The reaction continued at 0-5°C for 30 minutes, then the temperature was raised to 95-100°C over approximately 1.5 hours, and the reaction continued at 95-100°C for 4 hours. After cooling to room temperature, the supernatant was removed by decantation, and the mixture was washed twice with toluene to prepare a total volume of 58.0 L of toluene slurry. A portion of the obtained slurry components was sampled and its concentration was examined, revealing a slurry concentration of 248.0 g / L and an Al concentration of 1.21 mol / L.
[0110] Next, 12.6 mL of toluene and 0.6 mL (0.60 mL) of the slurry obtained above were charged into a 20 mL Schlenk tube that had been thoroughly purged with nitrogen. 1.8 mL (1.82 mL) of a 2 mM toluene solution of component (A-1) obtained in Synthesis Example 1 was added, and the mixture was contacted at a system temperature of 20-25°C for 1 hour to obtain a toluene slurry of the solid catalyst component (X-1).
[0111] <Synthesis Example 6> In Synthesis Example 5, the preparation was carried out in the same manner as in Synthesis Example 3, except that component (B-1) was used instead of component (A-1), to obtain a toluene slurry of the solid catalyst component (X-2).
[0112] <Synthesis Example 7> In Synthesis Example 5, the amount of 2mM toluene solution of component (A-1) added was changed to 0.9 mL (0.91 mL), and 0.9 mL (0.91 mL) of 2mM toluene solution of (B-1) was added after the toluene solution of component (A-1). Otherwise, the preparation was carried out in the same manner as in Synthesis Example 5 to obtain a toluene slurry of solid catalyst component (X-3).
[0113] <Synthesis Example 8> In Synthesis Example 5, the preparation was carried out in the same manner as in Synthesis Example 5, except that component (A-2) was used instead of component (A-1), to obtain a toluene slurry of the solid catalyst component (X-4).
[0114] <Synthesis Example 9> In Synthesis Example 5, the preparation was carried out in the same manner as in Synthesis Example 5, except that component (B-2) was used instead of component (A-1), to obtain a toluene slurry of the solid catalyst component (X-5).
[0115] <Synthesis Example 10> In Synthesis Example 5, the preparation was carried out in the same manner as in Synthesis Example 5, except that 1.64 mL of a 2 mM toluene solution of component (A-2) was added instead of 1.82 mL of a 2 mM toluene solution of component (A-1), and 0.18 mL of a 2 mM toluene solution of (B-2) was added after the addition of the toluene solution of component (A-2), to obtain a toluene slurry of solid catalyst component (X-6).
[0116] [Manufacturing Example 1] In a 1 L stainless steel autoclave equipped with stirring blades and thoroughly purged with nitrogen, 500 mL of heptane was added under a nitrogen atmosphere, and then ethylene was passed through to saturate both the liquid and gas phases with ethylene. Next, 0.150 mmol of triisobutylaluminum and 5.0 mL of toluene slurry of solid catalyst component (X-1) were charged in, and the temperature and pressure were increased to 80°C and 0.8 MPaG using ethylene gas, and the polymerization reaction was carried out for 90 minutes. After filtering the obtained polymer, it was vacuum-dried at 80°C for 10 hours to obtain 15.74 g of polyethylene.
[0117] [Manufacturing Example 2] In Production Example 1, the procedure was carried out in the same manner as in Production Example 1, except that 5.0 mL of toluene slurry of (X-2) was used instead of toluene slurry of solid catalyst component (X-1), and 9.42 g of polyethylene was obtained.
[0118] [Manufacturing Example 3] In Production Example 1, the procedure was carried out in the same manner as in Production Example 1, except that 5.0 mL of toluene slurry of (X-3) was used instead of toluene slurry of solid catalyst component (X-1), and 50.92 g of polyethylene was obtained.
[0119] [Manufacturing Example 4] In a 1 L stainless steel autoclave equipped with stirring blades and thoroughly purged with nitrogen, 500 mL of heptane was added under a nitrogen atmosphere, and then ethylene was passed through to saturate both the liquid and gas phases with ethylene. Next, 1.0 mL of 1-hexene, 0.150 mmol of triisobutylaluminum, and 5.0 mL of a toluene slurry of solid catalyst component (X-4) were charged in. Then, the temperature and pressure were increased to 80°C and 0.8 MPaG using an ethylene-hydrogen mixed gas with a hydrogen concentration of 0.45 vol%, and the polymerization reaction was carried out for 90 minutes. After filtering the obtained polymer, it was vacuum-dried at 80°C for 10 hours to obtain 8.17 g of ethylene-based polymer.
[0120] [Manufacturing Example 5] In Production Example 4, the procedure was carried out in the same manner as in Production Example 4, except that 5.0 mL of toluene slurry of (X-5) was used instead of toluene slurry of solid catalyst component (X-4), and 31.23 g of ethylene polymer was obtained.
[0121] [Manufacturing Example 6] In Production Example 4, the procedure was carried out in the same manner as in Production Example 4, except that 5.0 mL of toluene slurry of (X-6) was used instead of toluene slurry of solid catalyst component (X-4), and 18.33 g of ethylene polymer was obtained.
[0122] [Example 1] In a 1 L stainless steel autoclave with a stirring blade, which had been thoroughly purged with nitrogen, 500 mL of heptane was added under a nitrogen atmosphere, and then ethylene was passed through to saturate both the liquid and gas phases with ethylene. Next, 0.150 mmol of triisobutylaluminum, 1.5 mL of a 1 mg / mL toluene solution of dibutyl ether as component (D), and 5.0 mL of a toluene slurry of solid catalyst component (X-3) were charged in. The temperature and pressure were then increased to 80°C and 0.8 MPaG using ethylene gas, and the polymerization reaction was carried out for 90 minutes. After filtering the obtained polymer, it was vacuum-dried at 80°C for 10 hours to obtain 43.02 g of polyethylene.
[0123] [Example 2] In Example 1, the procedure was carried out in the same manner as in Example 1, except that the amount of 1 mg / mL toluene solution of dibutyl ether added was changed to 2.5 mL, and 25.65 g of polyethylene was obtained.
[0124] [Example 3] In a 1 L stainless steel autoclave with a stirring blade, which had been thoroughly purged with nitrogen, 500 mL of heptane was added under a nitrogen atmosphere, and then ethylene was passed through to saturate both the liquid and gas phases with ethylene. Next, 1.0 mL of 1-hexene, 0.150 mmol of triisobutylaluminum, 2.5 mL of a 1 mg / mL toluene solution of dibutyl ether as component (D), and 5.0 mL of a toluene slurry of solid catalyst component (X-6) were charged in. Then, the temperature was increased to 80°C and the pressure to 0.8 MPaG using an ethylene-hydrogen mixed gas with a hydrogen concentration of 0.45 vol%, and the polymerization reaction was carried out for 90 minutes. After filtering the obtained polymer, it was vacuum-dried at 80°C for 10 hours to obtain 11.25 g of ethylene-based polymer.
[0125] [Method for measuring the ratio of polymers derived from component (A) to polymers derived from component (B)] In the above-mentioned production example and embodiment, the ratio of polymers derived from component (A) and polymers derived from component (B) contained in the obtained polyethylene was determined by GPC peak separation as follows.
[0126] First, the molecular weight of the obtained polyethylene was measured by gel permeation chromatography (GPC). A gel permeation chromatograph HLC-8321GPC / HT (Tosoh Corporation) was used as the liquid chromatograph, with two TSKgel GMH6-HT columns and two TSKgel GMH6-HTL columns (both with an inner diameter of 7.5 mm and a length of 30 cm) as the separation columns. The column temperature was set to 140°C, and orthodichlorobenzene (containing 0.025% dibutylhydroxytoluene) was used as the mobile phase. The mobile phase was moved at a rate of 1.0 mL / min, the sample concentration was 0.15 mg / mL, the sample injection volume was 0.4 mL, and a differential refractometer was used as the detector. Calibration of the instrument was performed using monodisperse polystyrene (Tosoh Corporation). The relationship between retention time and signal intensity obtained from the above measurement was recorded as a chromatogram.
[0127] The molecular weight distribution curve (G1) obtained from the chromatogram (hereinafter sometimes referred to as "(G1)") was compared with the molecular weight distribution curve obtained by adding the molecular weight distribution curve (G2) of the polymer derived from component (A) (hereinafter sometimes referred to as "(G2)") and the molecular weight distribution curve (G3) of the polymer derived from component (B) (hereinafter sometimes referred to as "(G3)") in various proportions. Here, the molecular weight distribution curve obtained for the polyethylene obtained in Production Example 1 was used as the molecular weight distribution curve (G2) of the polymer derived from component (A), and the molecular weight distribution curve obtained for the polyethylene obtained in Production Example 2 was used as the molecular weight distribution curve (G3) of the polymer derived from component (B).
[0128] The aforementioned comparison was carried out specifically using the following procedure (S1) to (S5). (S1) For each of the numerical data in (G1), (G2), and (G3) above, the log (molecular weight) was divided into intervals of 0.02, and the intensity [d weight fraction / d log (molecular weight)] was normalized so that the area of the molecular weight distribution curve was 1.
[0129] (S2) For (G2), a constant a was added to all log (molecular weight), and all intensities were multiplied by an arbitrary multiplier x (where x is a real number greater than or equal to 0) to obtain the first molecular weight distribution curve (G2'). Here, a was determined so that the log (molecular weight) at the rise of the high molecular weight side in (G1) was the same as the log (molecular weight) at the rise of the high molecular weight side in (G2). Also, for (G3), a constant b was added to all log (molecular weight), and all intensities were multiplied by an arbitrary multiplier y (where y is a real number greater than or equal to 0) to obtain the second molecular weight distribution curve (G3'). Here, b was determined so that the log (molecular weight) at the rise of the low molecular weight side in (G1) was the same as the log (molecular weight) at the rise of the low molecular weight side in (G3). Then, the first molecular weight distribution curve (G2') and the second molecular weight distribution curve (G3') were added together to create the synthetic molecular weight distribution curve (GS).
[0130] (S3) The difference in intensity at each log (molecular weight) was calculated for the synthetic molecular weight distribution curve (GS) obtained in (G1) and (S2).
[0131] (S4) The difference obtained in (S3) was calculated for multiple magnifications x and y, while varying each of the magnifications x and y. Among these, it was determined that (G1) and the synthetic molecular weight distribution curve obtained in (S2) matched when the absolute value of the difference obtained in (S3) was less than 0.04.
[0132] (S5) The magnifications x and y when it was determined that they matched were converted to mass percent, and these were used as the ratio of polymer derived from component (A) to polymer derived from component (B). Based on the above comparison, The proportions of polymer derived from component (A) and polymer derived from component (B) in the polyethylene obtained in Production Example 3 were 7.2% by mass and 92.8% by mass, respectively. The proportions of polymer derived from component (A) and polymer derived from component (B) in the polyethylene obtained in Production Example 6 were 73.7% by mass and 26.3% by mass, respectively. The proportions of polymer derived from component (A) and polymer derived from component (B) in the polyethylene obtained in Example 1 were 9.4% by mass and 90.6% by mass, respectively. The proportions of polymer derived from component (A) and polymer derived from component (B) in the polyethylene obtained in Example 2 were 10.3% by mass and 89.7% by mass, respectively. The proportions of polymer derived from component (A) and polymer derived from component (B) in the polyethylene obtained in Example 3 were 80.6% by mass and 19.4% by mass, respectively. Each was calculated.
[0133] Table 1 shows the results of the above-mentioned production examples and examples. Figure 1 shows the relationship between the ratio of polymers derived from component (A) and component (B) obtained in Examples 1 and 2, and Production Example 3, and the amount of component (D) added. Figure 2 shows the relationship between the ratio of polymers derived from component (A-2) and component (B-2) obtained in Example 3 and Production Example 6, and the amount of component (D) added.
[0134] [Table 1]
[0135] Comparing Production Example 3 with Examples 1 and 2, and also comparing Production Example 6 with Example 3, it can be seen that as the amount of component (D) added increases, the proportion of polymer derived from component (B) in the obtained polyethylene decreases, and the proportion of polymer derived from component (A) increases. In other words, by using an additive, component (B) can be selectively deactivated, and the polymer formation of component (B) can be suppressed.
Claims
1. A method for producing an olefin polymer, characterized by comprising the step of (co)polymerizing ethylene and one or more olefins selected from the group consisting of 3 to 20 carbon atoms in the presence of an olefin polymerization catalyst comprising the following components (A), (B), and (C), and the following component (D). Component (A): A hafnium compound represented by the following general formula (9) or a hafnium compound represented by the following general formula (11); 【Chemistry 1】 [In general formula (9), n is a number that satisfies the valence of Hf, Q 1 This is a divalent group, which is a hydrocarbon group having 1 to 20 carbon atoms, a halogen-containing group, a silicon-containing group, a germanium-containing group, or a tin-containing group, and the hydrocarbon group having 1 to 20 carbon atoms may contain oxygen. Each of X is an atom or group independently selected from the group consisting of hydrogen atoms, halogen atoms, hydrocarbon groups, halogen-containing hydrocarbon groups, silicon-containing groups, oxygen-containing groups, sulfur-containing groups, nitrogen-containing groups, and phosphorus-containing groups, and may be the same or different from each other. 【Chemistry 2】 [In general formula (11), n is a number that satisfies the valence of Hf, Q1 is a divalent group, which is a hydrocarbon group having 1 to 20 carbon atoms, a halogen-containing group, a silicon-containing group, a germanium-containing group, or a tin-containing group, and the hydrocarbon group having 1 to 20 carbon atoms may contain oxygen. Each of X is an atom or group independently selected from the group consisting of hydrogen atoms, halogen atoms, hydrocarbon groups, halogen-containing hydrocarbon groups, silicon-containing groups, oxygen-containing groups, sulfur-containing groups, nitrogen-containing groups, and phosphorus-containing groups, and may be the same or different from each other. Component (B): A zirconium compound represented by the following general formula (10) or a zirconium compound represented by the following general formula (12); 【Transformation 3】 [In general formula (10), n is a number that satisfies the valence of Zr, Q 2 This is a divalent group, which is a hydrocarbon group having 1 to 20 carbon atoms, a halogen-containing group, a silicon-containing group, a germanium-containing group, or a tin-containing group, and the hydrocarbon group having 1 to 20 carbon atoms may contain oxygen. Each of X is an atom or group independently selected from the group consisting of hydrogen atoms, halogen atoms, hydrocarbon groups, halogen-containing hydrocarbon groups, silicon-containing groups, oxygen-containing groups, sulfur-containing groups, nitrogen-containing groups, and phosphorus-containing groups, and may be the same or different from each other. 【Chemistry 4】 [In general formula (12), n is a number that satisfies the valence of Zr, Q2 is a divalent group, which is a hydrocarbon group having 1 to 20 carbon atoms, a halogen-containing group, a silicon-containing group, a germanium-containing group, or a tin-containing group, and the hydrocarbon group having 1 to 20 carbon atoms may contain oxygen. Each of X is an atom or group independently selected from the group consisting of hydrogen atoms, halogen atoms, hydrocarbon groups, halogen-containing hydrocarbon groups, silicon-containing groups, oxygen-containing groups, sulfur-containing groups, nitrogen-containing groups, and phosphorus-containing groups, and may be the same or different from each other. Component (C): At least one compound selected from the group consisting of organometallic compounds (c-1), organoaluminum oxy compounds (c-2), and compounds (c-3) that react with components (A) and (B) to form ion pairs, represented by the following general formulas (3) to (5); R a m Al(OR b ) n H p X q ・・・(3) [In general formula (3), R a and R b each independently represent a hydrocarbon group having 1 to 15 carbon atoms, X represents a halogen atom, m is a number satisfying 0 < m ≤ 3, n is a number satisfying 0 ≤ n < 3, p is a number satisfying 0 ≤ p < 3, q is a number satisfying 0 ≤ q < 3, and m + n + p + q = 3.]] M a AlR a 4 ・・・(4) [In general formula (4), M a represents Li, Na, or K, and R a This indicates a hydrocarbon group with 1 to 15 carbon atoms. R a r M b R b s X t ・・・(5) [In general formula (5), R a and R b Each independently represents a hydrocarbon group with 1 to 15 carbon atoms, M b [where X is selected from Mg, Zn, and Cd, X represents a halogen atom, r is 0 < r ≤ 2, s is 0 ≤ s ≤ 1, t is 0 ≤ t ≤ 1, and r + s + t = 2.] Component (D): Compound represented by the following general formula (6); R 17 -E-R 18 ・・・(6) [In general formula (6), E represents an oxygen atom or a sulfur atom, and R 17 and R 18 Each of these independently represents an alkyl group having 1 to 20 carbon atoms.
2. In the above general formula (6), R 17 and R 18 The method for producing an olefin polymer according to claim 1, wherein each of them is independently a linear alkyl group having 1 to 20 carbon atoms.
3. In the above general formula (6), R 17 and R 18 A method for producing an olefin polymer according to claim 1 or 2, wherein is a linear alkyl group having the same number of carbon atoms from 1 to 20.
4. A method for producing an olefin polymer according to any one of claims 1 to 3, wherein the catalyst for olefin polymerization is in solid form.
5. The method for producing an olefin polymer according to claim 4, wherein the catalyst for olefin polymerization further comprises a solid support (S).
6. The method for producing an olefin polymer according to claim 5, wherein the component (C) is an organoaluminum oxy compound and the solid carrier (S) is a porous oxide.
Citation Information
Patent Citations
Catalyst system for olefin polymerization and olefin copolymerization
JP1989074202A
Ethylenic copolymer and production thereof
JP1990276807A
Method for producing ethylene / olefin copolymer
JP2003501526A
Method for producing ethylene / olefin copolymer
JP2003501527A
Process for producing olefin polymer
JP2014019825A